Studi Kelayakan Bisnis dalam Rangka Pendirian XX Cafe - Widra Kristian; Felix Indrawan (Universitas Kristen Maranatha, 2019)
One of the rapidly developing creative industries in Indonesia is the food and beverage or culinary industry. Currently the food and beverage industry is the sector with the largest contribution of the Indonesian economy, namely 5.5 percent of national gross domestic product and 31 percent of gross domestic product in the non-oil and gas processing industry. This makes Indonesia a high potential in the culinary field. Seeing the rapid development of the culinary world in Indonesia, more and more restaurants, cafes, or eating places are emerging in Indonesia.This study aims to examine the business profile of XX Cafe, analyze the prospects of XX Cafe business on Jl. Cihampelas, Bandung Wetan, Bandung City, West Java based on business feasibility aspects such as: legal aspects, environmental aspects, market and marketing aspects, technical and technological aspects, aspects of human resources, and financial aspects. In conducting this research, the author discusses more deeply the financial aspects. These financial aspects are analyzed using capital budgeting techniques that take into account the return period, present net value, internal rate of return, and profit index. The results of calculating capital budgeting techniques can be a consideration for investors to make decisions. After the analysis and calculation was made, XX Café is feasible to run. But apart from the results of the calculation, a capital budgeting control is also needed so that the expectations that have been made can be achieved. Keywords: Feasibility Study, Payback Period, Internal Rate of Return, Net Present Value, Profitability Index